Effect of shading on growth of stock plants and subsequent rooting of cuttings of aquilaria microcarpa baill - Soon, Chee Pei (Universiti Malaysia Sarawak (UNIMAS), 2012)
The study on the growth performance of Aquilaria microcarpa Baill. under different light intensity and subsequently used as rooting of cuttings was conducted in University Malaysia Sarawak (UNIMAS) External Laboratory. Growth of stock plants was observed for duration of 16 weeks and then for cuttings in ten-week duration. Under the shading experiment, stock plants were kept under 0%, 50%, and 75% of shades. Stock plants under 50% shading showed the greatest mean height increment recorded (12.87 cm). This was followed by 75% shading (12.66 cm) and 0% shading (7.11 cm). Stock plants that showed the highest mean diameter increment was grown under 50% shading too (2.17 mm), followed by 75% shading (1.75 mm) and 0% shading (1.11 mm). Stock plants from 75% shading obtained the highest mean root weight ratio (0.38 ± 0.04 g/g) while stock plants from 50% shading had the highest mean shoot weight ratio (0.53 ± 0.04 g/g). Stock plants from 75% shading also recorded the highest root shoot ratio (0.78 ± 0.01 g/g). Cuttings taken from stock plants under 75% shade showed the highest rooting percentage (6.67%). The rooting percentage of cuttings taken from 0% and 50% shades were recorded the same which was 5% when the experiment terminated. Cuttings from 75% shading had 15% rooted in treatment without hormone, 5% rooted in treatment with K-IBA 200 mg/L.